2020
DOI: 10.1016/j.vaccine.2020.09.084
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver willingness to vaccinate their children against COVID-19: Cross sectional survey

Abstract: Highlights About two thirds of caregivers intend to vaccinate their children against COVID-19. Most common reason for acceptance was to protect the child. Most common reason for refusal was the vaccine’s novelty. Child age, chronic illness, vaccination history affects willingness. Caregiver gender, vaccination history, concern about infection affect willingness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

46
383
15
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 301 publications
(488 citation statements)
references
References 24 publications
46
383
15
3
Order By: Relevance
“…All except seven had national/state representative samples through random selection from the targeted population (e.g., via voter registration or phone numbers) or large national/international opt-in panels, many stratified by demographics. The other seven were convenience samples utilizing social media [2,7,[16][17][18] or recruiting posters [19,20].…”
Section: Search Results and Survey Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…All except seven had national/state representative samples through random selection from the targeted population (e.g., via voter registration or phone numbers) or large national/international opt-in panels, many stratified by demographics. The other seven were convenience samples utilizing social media [2,7,[16][17][18] or recruiting posters [19,20].…”
Section: Search Results and Survey Characteristicsmentioning
confidence: 99%
“…The impacts of having been infected oneself or knowing a friend/family who had and the desire to protect oneself or others were also cited but less conclusive. Some studies indicated positive association [19,53], while others found no correlation [21]. One study reported only 55% of those worrying about themselves or family members getting infected would get vaccinated [49].…”
Section: Vaccine Attributes and Individual Factorsmentioning
confidence: 99%
See 3 more Smart Citations